Online mindfulness therapy as a smoking cessation aid in Malaysia: A randomized control trial - Hemanath Sinnathamby; Fredie Robinson; Nicholas Pang Tze Ping; Lim Eng Kean; Ong Shi Joe; Alyssa Suraya; Joshua Selvaraj; Lau Jia Qi; Lim Yong Xin; Vanushya Alagasan (Malaysian Public Health Physicians Association, 2023)
Effective smoking cessation programs are crucial in helping smokers to achieve cessation, indirectly reducing smokingrelated morbidity and mortality. Several studies have shown promising results using mindfulness therapy and online platforms in smoking cessation. This study assesses the effectiveness of online mindfulness therapy (MT) as an aid in smoking cessation programmes compared with standardized behavioural approaches (SBA). A randomized control trial with a single-blind, two-group design was chosen, with assessment at baseline. Participants were recruited by advertising on social media platforms and accepted according to the eligibility criteria. The participants who fit the eligibility criteria were randomized and divided into two groups. Each group received three sessions of online therapy (MT or SBA) every 2 weeks with one telephone call each week as a reinforcement. Participants filled in questionnaires at baseline and end of the intervention (1st week and 5th week). The data was analyzed using Generalized Estimating Equation (GEE). The number of cigarettes smoked per day post-intervention was significantly lower in the MT group compared with the SBA group (β: -3.50, 95% CI -4.62 to -2.39, p-value: < 0.001). The MT group recorded low Fagerstrom nicotine dependence tests at the end of the study, compared to low to moderate scores in the SBA group (β: -1.82, 95% CI –2.31 to -1.33, p-value: < 0.001). Furthermore, participants in the MT group reduced their urge to smoke more than the SBA group (β: -2.44, 95% CI -3.76 to -1.12, p-value: < 0.001). In conclusion, online MT is more effective in helping smokers in reducing the number of cigarettes smoked per day, nicotine dependence, and urge for smoking compared to SBA. Further follow-up studies using online platforms should be conducted to compare the effectiveness of online MT longitudinally.